Improv Theater and Whiteness in Education: A Systematic Literature Review. (February 2023) - Tanner, Samuel J.; McCloskey, Andrea
Improv theater has expanded beyond a popular American form of entertainment into an educational experience for students and teachers. It may be difficult to imagine that an interactive, joyful, and collaborative improv workshop might be harmful, but our own experiences as professional improvisers led us to observe that even well-intentioned, antiracist improv theater interventions tend to reflect Whiteness more than democratic values. We investigate this observation through a systematic review of education research articles. Our review of 30 studies reveals that, to varying degrees, researchers have regarded improvisation as an instrumental practice to improve some other activity or as metaphor for the activity of teaching. We found that Whiteness has been central to the use of improvisation in educational contexts. Finally, this study illustrates that a turn toward disciplined improvisation or an improvisational ethos offers one way to practice the ideals of democratic education.